Effect of preoperative analgesics and cooled Lidocaine with Epinephrine on the anesthetic efficacy of inferior alveolar nerve block in patients with symptomatic irreversible pulpitis: A single-blind, randomized controlled trial - Prabhu, V Solomon; Borugadda, Roopesh; Neelima, U Lavanya; Reddy, Ch Priyanka; Nuka, Aswini; Kondipudi, Nimisha (International Journal of Dental Materials, 2024)
Background: Treating mandibular molars with symptomatic irreversible pulpitis poses challenges, as achieving anaesthesia in “hot teeth” is difficult. Epinephrine aids anaesthesia by reducing blood absorption through local vasoconstriction. However, when epinephrine is contraindicated, cooling the anaesthetic may provide effective vasoconstriction in cutaneous arteries and inhibit sensory nerve action potentials, enhancing anaesthetic efficacy. Aim: To evaluate the effectiveness of preoperative analgesics and cooling of 2% lidocaine solution with 1:200,000 Epinephrine on the efficacy of Inferior alveolar nerve block (IANB) during root canal treatment in patients with symptomatic irreversible pulpitis of the mandibular molars. Materials and methods: This study was conducted on 36 subjects diagnosed with symptomatic irreversible pulpitis. Participants were randomly assigned into one of three groups, each consisting of 12 patients (n=12). The subjects in Group A (Control) received Vitamin E 400 mg tablets as premedication and Local Anaesthetic injection of 2% Lignocaine at room temperature. The subjects in Group B received Piroxicam 20 mg tablets as premedication and local anaesthetic injection of 2% Lignocaine at Room Temperature. The subjects in Group C received Piroxicam 20 mg tablets as premedication and local anaesthetic injection of 2% Lignocaine at 4° Celsius. The patient’s preoperative pain levels before and after administering the analgesic, before and after the administration of local anaesthesia and intraoperative pain levels were recorded using the Heft-Parker visual analogue scale. Anaesthetic success was again evaluated after re-initiation of the endodontic treatment. The heart rates of the patients were measured using a finger pulse oximeter. Results: The patients in group C showed the highest mean difference in pain levels followed by group B and A. However, the Group A patients displayed the highest heart rates followed by Groups B and C. One-way ANOVA showed a significant differences in the pain levels (p=0.0002) and heart rates (p=0.0004) among the groups. Conclusion: This study showed that Piroxicam effectively achieved IANB in patients with symptomatic irreversible pulpitis of mandibular molars. Cooling 2% lidocaine with 1:200,000 epinephrine to 4°C significantly reduced post-injection heart rate and enhanced anesthetic success.